Deciphering the role of miRNA-mRNA interactions in cerebral vasospasm post intracranial hemorrhage - Chu, Xiang; Zhu, Xiyan; Xu, Honghao; Zhao, Wenbing; Guo, Debin; Chen, Xing; Wu, Jinze; Li, Lei; Wang, Hao; Fei, Jun (Frontiers in Molecular Biosciences, 2025)
Cerebral vasospasm (CVS), a serious complication following subarachnoid hemorrhage, is associated with high rates of mortality and disability. Emerging evidence suggests that abnormal miRNA and mRNA are involved in the development of CVS. This study aims to identify essential miRNA-mRNA regulatory pairs that contribute to CVS pathogenesis. We compared the differences between spasm and non-spasm groups after cerebral hemorrhage, identifying 183 differentially expressed genes (DEGs) and 19 differentially expressed miRNAs (DEMs) related to cerebral vasospasm from the GEO database. Further functional enrichment and KEGG analysis revealed that these DEGs were enriched in several terms and pathways, including the PI3K/AKT/mTOR signaling pathway, oxidative phosphorylation pathway, RNA degradation, and folate biosynthesis signaling pathway. By employing the degree scores method for each gene, we identified the top 10 genes and developed a protein-protein interaction (PPI) network. Additionally, we discovered 19 DEMs associated with CVS and integrated them with mRNA dataset analysis to construct a miRNA-mRNA network, which comprised 8 functionally differentially expressed DEMs and 6 target mRNAs. Experimental validation confirmed the significant regulatory roles of four miRNAs (Let-7a-5p, miR-24-3p, miR-29-3p, and miR-132-3p) and two mRNAs (CDK6 and SLC2A1) in the pathogenesis of CVS. In conclusion, this comprehensive study identifies pivotal miRNAs and their target mRNAs associated with CVS through an integrated bioinformatics analysis of miRNA-mRNA co-expression networks. This approach elucidates the intricate molecular mechanisms underlying CVS and uncovers potential therapeutic targets, thereby providing a valuable foundation for refining and optimizing future treatment strategies.